Community Education on Anxiety Management Facing Covid-19 Pandemic in Alue Awe Village, Muara Dua District, Lhokseumawe City - Syahabuddin Syahabuddin; Ainil Yusra; Subki Subki; Munawatun Haya; Mulia Ulfitri; Yuli Apriani (Ridwan Institute, 2022)
Corona Virus Disease 2019 or COVID-19 has become the world's spotlight because of its rapid and widespread spread in a relatively short time, so People around the world are becoming more aware of the transmission of this virus. The number of deaths due to this virus is increasing day by day. The increasing number of deaths and difficulties caused by COVID-19 have also resulted in several people experiencing increased and prolonged fear and anxiety. To help people adapt to the anxiety and stress they face during the COVID-19 pandemic, education about various ways to reduce anxiety and stress needs to be done. Increased knowledge will increase people's behaviour in reducing anxiety and stress during the COVID-19 pandemic. This study aims to improve community knowledge and skills to manage anxiety in the face of the Covid-19 pandemic in Alue Awe Village, Muara Dua District, Lhokseumawe City. Method of study is community service is conducted through face-to-face methods/health education, distributing leaflets and demonstrations. The initial survey was conducted by distributing questionnaires about the impact of Covid-19 to measure the level of public knowledge. The results show that average value of public knowledge about covid-19 and how to reduce anxiety during a pandemic during the pre-test was